2021
DOI: 10.1590/0102-672020210002e1620
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Complications of Coronavirus Disease (Covid-19)

Abstract: Background: It is currently understood that severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) directly enters target cells by binding to the angiotensin-converting enzyme 2 (ACE2) receptor. Accordingly, tissues with high expression levels of ACE2 are more susceptible to infection, including pulmonary alveolar epithelial cells, small intestine enterocytes, cholangiocytes, and vascular endothelial cells. Considering the atypical manifestations of COVID-19 and the challenges of early diagnosis, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…In addition to the important role of ACE-2 receptors, patients with COVID-19 may develop coagulopathy and vasculopathy, as well as resulting endothelial dysfunction and thrombosis 8 , 10 , 11 , 17 , 18 , 24 . COVID-19-associated coagulopathy (CAC) is characterized by increased D-dimer and fibrinogen levels, which can lead to thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the important role of ACE-2 receptors, patients with COVID-19 may develop coagulopathy and vasculopathy, as well as resulting endothelial dysfunction and thrombosis 8 , 10 , 11 , 17 , 18 , 24 . COVID-19-associated coagulopathy (CAC) is characterized by increased D-dimer and fibrinogen levels, which can lead to thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar que os sintomas de febre e falta de ar, conforme demonstrado nos nossos resultados, afetaram a grande maioria dos indivíduos que apresentaram parosmia pós-COVID, parecem ser fortes indicativos e preditivos para ocorrência da doença. Tal constatação se deve ao fato de que o vírus SARS-CoV-2 possui a capacidade de infectar os neurônios humanos de forma direta, o que faz com que os tecidos infectados com altos níveis de ECA2 fiquem suscetíveis, tais como as células epiteliais dos alvéolos pulmonares 4 . O desequilíbrio entre as citocinas, vindo do estado pró-inflamatório e mudança na resposta imune adaptativa e inata, causa importantes alterações na atividade e desenvolvimento leucocitário 15 , o que pode justificar a elevada prevalência de parosmia no presente estudo, cujo IMC médio foi de sobrepeso.…”
Section: Discussionunclassified
“…Estudos revelam que o vírus SARS-CoV-2 pode infectar, de forma direta, as células-alvo, por acoplamento ao receptor da enzima conversora de angiotensina 2 (ECA2), o que ocasiona maior susceptibilidade à infecção pelos tecidos com altos níveis de ECA2, tais como as células epiteliais dos alvéolos pulmonares, os enterócitos do intestino delgado, os colangiócitos e o endotélio vascular. Além disso, a regulação da resposta inflamatória é influenciada pela ECA2, distribuindo-se nos órgãos abdominais, o que pode explicar a ocorrência de sintomas extrapulmonares em alguns pacientes 4 .…”
Section: Introductionunclassified
“…Other gastrointestinal symptoms, such as vomiting, diarrhea, and abdominal pain simulating inflammatory acute abdomen, have been described with COVID-19 and may occur before or even in the absence of respiratory symptoms 9 , 10 , 11 . It was observed that the patient in case 1 presented outputs of up to 4 L daily, which may be related to the diarrhea caused by SARS-COV-2.…”
Section: Discussionmentioning
confidence: 99%